On a class of Kirchhoff-Choquard equations involving variable-order fractional $p(·)$-Laplacian and without Ambrosetti-Rabinowitz type condition - Biswas, Reshmi; Tiwari, Sweta (Topological Methods in Nonlinear Analysis, 2021)
In this article, we study the existence of weak solutions and of ground state solutionsusing the Nehari manifold approach, and existence of infinitely many solutions using the fountain theorem and the dual fountain theorem for a class of doubly nonlocal Kirchhoff-Choquard type equationsinvolving the variable-order fractional $p(·)$-Laplacian operator. Here the nonlinearity does not satisfy the well known Ambrosetti-Rabinowitz type condition.